Controlled inactivation of Trichophyton rubrum using shaped electrical pulse bursts: Parametric analysis. (27th April 2016) - Novickij, Vitalij; Grainys, Audrius; Švedienė, Jurgita; Paškevičius, Algimantas; Novickij, Jurij
Abstract : The dermatophytes infect the skin by adherence to the epidermis followed by germination, growth, and penetration of the fungal hyphae within the cells. The aim of this study was to investigate the efficacy of the pulsed electric fields (PEF) of controlled inactivation of Trichophyton rubrum (ATCC 28188). In this work, we have used bursts of the square wave PEF pulses of different intensity (10–30 kV/cm) to induce the irreversible inactivation in vitro. The electric field pulses of 50 µs and 100 µs have been generated in bursts of 5, 10, and 20 pulses with repetition frequency of 1 Hz. The dynamics of the inactivation using different treatment parameters were studied and the inactivation map for the T. rubrum has been defined. Further, the combined effect of PEF with the antifungal agents itraconazole, terbinafine, and naftifine HCl was investigated. It has been demonstrated that the combined effect results in the full inactivation of T. rubrum colony. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1056–1060, 2016